Polymer Synergy in Action: Antimicrobial Properties of Chitosan-Alginate Complexes against Diverse Bacterial Strains - Sanchita Mandal (International Journal of Pharmaceutical & Biological Archive, 2025)
This study investigates the formation and antimicrobial properties of polyelectrolyte complexes (PECs) made from chitosan with sodium alginate (CS-SA) and CS-carboxylated SA (CS-CMA). The research compares their effectiveness against Gram-positive and Gram-negative bacteria, exploring how polymer modifications affect antimicrobial activity.